2020
DOI: 10.1177/1744806920964360
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord stimulation using differential target multiplexed programming modulates neural cell-specific transcriptomes in an animal model of neuropathic pain

Abstract: Spinal cord stimulation is a proven effective therapy for treating chronic neuropathic pain. Previous work in our laboratory demonstrated that spinal cord stimulation based on a differential target multiplexed programming approach provided significant relief of pain-like behavior in rodents subjected to the spared nerve injury model of neuropathic pain. The relief was significantly better than obtained using high rate and low rate programming. Furthermore, transcriptomics-based results implied that differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 17 publications
4
58
0
1
Order By: Relevance
“…29,30 Analysis of neuron-specific and glia-specific gene expression in a rodent model demonstrated that treatment with DTMP modulated gene expression of such cell-specific transcriptomes toward levels found in naïve animals. 18 This supported the hypothesis that DTM SCS provides analgesia by balancing pain-related biological processes, such as neuroinflammation and ion transport, which involve neuron-glial interaction that had been affected by the establishment of neuropathic pain. 17…”
Section: Other Outcomessupporting
confidence: 66%
“…29,30 Analysis of neuron-specific and glia-specific gene expression in a rodent model demonstrated that treatment with DTMP modulated gene expression of such cell-specific transcriptomes toward levels found in naïve animals. 18 This supported the hypothesis that DTM SCS provides analgesia by balancing pain-related biological processes, such as neuroinflammation and ion transport, which involve neuron-glial interaction that had been affected by the establishment of neuropathic pain. 17…”
Section: Other Outcomessupporting
confidence: 66%
“…These findings support the hypothesis that SCS stimulation parameters influence microglial activation and offer potential insight into the outcomes of DTMP in animal studies. 6 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…For many years, the gate control theory served as the putative mechanism of action for the analgesic effects of SCS ( Melzack and Wall, 1965 ). Later work has employed bioinformatics and proteomics to elucidate the susceptibilities of the biochemical and molecular pathways of pain to SCS ( Vallejo et al, 2016 ; Cedeño et al, 2020 ; Tilley et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%